2022
DOI: 10.1371/journal.pone.0263662
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the contralateral effects of unilateral peripheral stimulation on neuromuscular function

Abstract: It is known that resistance exercise using one limb can affect motor function of both the exercised limb and the unexercised contralateral limb, a phenomenon termed cross-education. It has been suggested that cross-education has clinical implications, e.g. in rehabilitation for orthopaedic conditions or post-stroke paresis. Much of the research on the contralateral effect of unilateral intervention on motor output is based on voluntary exercise. This scoping review aimed to map the characteristics of current l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 109 publications
2
15
1
Order By: Relevance
“…The measured contralateral force transfer can also be seen as confirmation of the inclusion of neuronal aspects in the stretching-induced MSt increases. Zhou et al [ 29 ] referred to different methods of peripheral stimulation, e.g., electrical stimulation or vibration training to induce cross-educational effects; however, the underlying mechanisms remain unclear. Based on the current literature, the authors hypothesize that peripheral sensory inputs might play an important role in inducing contralateral force transfer effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The measured contralateral force transfer can also be seen as confirmation of the inclusion of neuronal aspects in the stretching-induced MSt increases. Zhou et al [ 29 ] referred to different methods of peripheral stimulation, e.g., electrical stimulation or vibration training to induce cross-educational effects; however, the underlying mechanisms remain unclear. Based on the current literature, the authors hypothesize that peripheral sensory inputs might play an important role in inducing contralateral force transfer effects.…”
Section: Discussionmentioning
confidence: 99%
“…Since neither imaging techniques (such as sonography or magnetic resonance imaging) were used to assess muscle hypertrophy, nor were EMG measurements conducted to quantify changes in neuronal innervation, the physiological factors of the increased MSt, as well as the cross-education effects, remain unclear. As Manca et al [ 50 ] highlighted a variety of possible explanations and Zhou et al [ 29 ] referred to the need for clarification regarding the underlying mechanisms of contralateral effects due to unilateral peripheral stimulation, further studies should include additional measuring procedures to gain more insights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that long duration static stretching sessions implemented for 6 weeks resulted in moderate to large magnitude MSt increases of 14.2%-22.3% (d = 0.51-0.91), increases in MTh and ROM of 15.3% (d = 0.84) and 13.2%-27.3% (d = 0.47-0.87) dependent on used knee joint angle, respectively (Warneke et al, 2022b;Warneke et al, 2022c). Interestingly, previous studies also showed significant cross-education effects in response to stretching interventions of up to 12 weeks regarding MSt (Nelson et al, 2012;Warneke et al, 2022b;Warneke et al, 2022c), which might be attributed to neuronal adaptations induced by increased activity of stretch reflex afferents (Zhou, 2000;Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 95%
“…The contralateral force transfer is well known from strength training routines (Lee and Carroll, 2007;Manca et al, 2021). An explanatory approach of Zhou (2000Zhou ( , 2022 attributes increases in the contralateral leg with afferent signals induced by different training routines, which could be present without a central innervation of the muscle by voluntary contraction. This may be of an importance because no voluntary contraction can be assumed in passive stretch.…”
Section: Long-term Effects Of Stretchingmentioning
confidence: 99%